Skema Pelembagaan Antara Kelurahan Wiyung Dengan Kader Jumantik Dalam Gerakan Pemberantasan Sarang Nyamuk - Istian, Amilia Nur; Ma’ruf, Muhammad Farid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Dengue fever is a disease that still occurs frequently and is classified as high in Indonesia caused by the bite of the aedes aegypti mosquito. In East Java Province, in 2024 it reached 29,496 cases while in Surabaya City it increased by 20.94% from the previous year. The mosquito nest eradication movement is an activity to stop the breeding of dengue fever mosquitoes. The implementation of this movement involves several parties who coordinate with each other. The implementation of mosquito nest eradication in Wiyung Village runs routinely every week by monitoring residents' houses carried out by jumantik cadres and the village. The purpose of this study was to determine and describe the coordination process between Wiyung Village and Jumantik Cadres and identify obstacles in the implementation of coordination using qualitative descriptive research types through narrative analysis techniques and focusing on the coordination process carried out by stakeholders using coordination theory according to Hasibuan (2011:88) which consists of unity of action, communication, division of labor and discipline. The results of the study showed that the coordination process carried out had run smoothly every week. However, there are findings in this study, namely several houses found in the location are not local residents so that cadres continue to monitor even though they do not match the data in the application, There are cadres who disagree in a routine gathering forum in one of the RW, All Surabaya Hebat Cadres participate in jumantik and posga activities so that work specialization is only in the form of dividing the area and the discussion of the division of work is not focused on jumantik activities alone but also other activities, The number of cadres in each area is not evenly distributed, village assistance is not routine, the coordinator has not implemented strict discipline to its members, and there are members who arrive late but have previously asked for permission.